If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 0.25y = 1 Solving 5 + 0.25y = 1 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 0.25y = 1 + -5 Combine like terms: 5 + -5 = 0 0 + 0.25y = 1 + -5 0.25y = 1 + -5 Combine like terms: 1 + -5 = -4 0.25y = -4 Divide each side by '0.25'. y = -16 Simplifying y = -16
| 1+7=n | | p+6=3 | | -15n+8=-11n-16 | | n+5=15 | | 1.4b+10=-8 | | -16=.5s-20 | | 125x^3+1=25x^2+5x | | 3(9+4)=3(9)+3(4) | | 12+4-x=10 | | 7p-3p-4=-4p+2+10 | | -2+4=m-10 | | 2(2a+3)=-(a+6) | | -10=.6y-1 | | -2+x=7x+2 | | 6y+8=3y-16 | | v^3-81v^2-4v+324=0 | | 6v^2-6f^2=0 | | 8-x=28 | | -4+11=16x-3-15x | | 3(2-1d)+5d=7 | | -3x-24=-6(4x-3) | | (2y+11)-y=25 | | -25+a^2=0 | | y=x^2-3x-21 | | 32+3y-10=13y-14-4y | | 1+4k=7+5k | | (2)(-3)-2(2)(3)= | | -b^3-10b^2-25b=0 | | 7x^4+4=29x^2 | | -4(-8+5x)-4=-6(x-7) | | 96w^2+336w+294=0 | | 2(3x-4)-6=3x-1 |